PENGEMBANGAN MEDIA PERMAIANAN ULAR TANGGA KOTAK TIGA DIMENSI SEBAGAI MEDIA PEMBELAJARAN KOSAKATA DAN KALIMAT DASAR BAHASA JEPANG - Rachel Oktariatie Harahap; Hadriana Hadriana; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aimed to find out what are the procedures carried out in making developed game media "The three-dimensional ladder snake box and whether it is an expert standard or validator so that it is worthy of being used as a learning medium. This type of research uses the R & D (Research and Development) model using the Sugiyono development model. The subjects of this study were the tenth grade students of Pekanbaru Integrated Vocational High School, totaling 20 students. The data collection techniques is carried out by using questionnaires. The results showed five stages: a) Potential Problems b) Data Collection, c) Planning, d) Product Design, e) Product Validation. The level of feasibility of the Three Dimensional Box Ladder Snake Media Game As A Media Learning Japanese Vocabulary and Basic Sentences based on 3 validators consisting of material experts, media and teachers of the Pekanbaru Integrated Vocational High School. The Three Dimensional Box Ladder Snake Game Media As A Media For Vocabulary Learning and Basic Japanese Language Sentences is said to be feasible, based on the results of the validation by material experts is in average score of 77.7% with a fairly decent category, media experts is an average score of 96.8% in the category of very decent, and teachers of Pekanbaru Integrated Vocational High School is 96.8% with a very decent category. After getting the validation results, the product revision is conducted according to the suggestions and input from the validator so that the product becomes better and is suitable to use in Japanese vocabulary learning.Key Words : Three Dimensional Box Ladder Snake